KETIDAKPASTIAN KEBIJAKAN EKONOMI CHINA DAN PERTUMBUHAN EKONOMI INDONESIA - Wilantari, Regina Niken; Oktaviana, Faradilla; Santoso, Edy; Yunitasari, Duwi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2020)
Global economic policy uncertainty will influence economic stability among countries integrated into international trade. The trade war between America and China has affected the weakening of macroeconomic indicators in developing countries, one of which is Indonesia. The objective of this study is to examine the influence of China's economic policy uncertainty and macroeconomic indicators, i.e., inflation, investment, and Brent oil price, on Indonesia's economic growth. Research data were secondary time series data taken from the Q1 2009-Q4 2018 quarterly period. The method of analysis used is the Vector Error Correction Model (VECM). Results showed that in the long run, the uncertainty of China's economic policy and Brent oil price could negatively influence Indonesia's economic growth. On the other hand, inflation, in the long run, had a positive and significant influence on Indonesia's economic growth. Meanwhile, investment did not have a significant influence on Indonesia's economic growth. Keywords: economic growth, uncertainty of economic policy, Vector Error Correction Model